The Influence of Digital Literacy, Security and Brand Image Through the Customer Interest of Using the Muamalat DIN Application (Case Study at Bank Muamalat Sub Branch Boyolali) - Ardiyansyah, Muhammad; Abdullah, Agung (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
The aims of this study are to see whether or not digital literacy, security, and brand image are affected by customer interest in using Muamalat DIN. This research is based on the use of the Muamalat DIN application issued by Bank Muamalat which is few about only around 37% of all customers in a Sub Branch. This type of research is quantitative research with a SEM-PLS approach and the primary data is the data used in this study which was obtained from the distribution of questionnaires and online to customers of Bank Muamalat Sub Branch Boyolali. The sample of this study was taken using a simple random sampling technique and the Taro Yamane formula was used to calculate the number of samples used. The results of the study show that digital literacy does not have a significant effect on customer interest in using Muamalat DIN at Bank Muamalat Sub Branch Boyolali. Meanwhile, security and brand image have a significant effect on customer interest in using Muamalat DIN at Bank Muamalat Sub Branch Boyolali.